Case Study: The Permanent Pacemaker in Managing Sinus Node Dysfunction in a Patient with a History of CAD post PCI - Ines Nur Syabani; Ignatius Yansen NG; Muhamad Arif Budiman; Nurhayati Nurhayati; Erlina Pudyastuti (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Sinus Node Dysfunction (SND) is an arrhythmia characterized by rhythm abnormalities in the heart. The incidence of SND increases with age due to degenerative changes in the sinoatrial node. Symptoms of SND are often subtle and nonspecific, leading to diverse ECG findings. In patients with a history of coronary artery disease (CAD), post-percutaneous coronary intervention (PCI), managing SND can be challenging. The primary treatment for SND is Permanent Pacemaker (PPM) implantation, which delivers electrical pulses to the myocardium to correct rhythm abnormalities. The results of the patient's ECG evaluation have improved, as indicated by the regular PR interval and QRS complex following PPM installation. The patient's heart rate increased by 44.7% after the PPM was inserted. In patients with SND and a history of CAD after PCI, Permanent Pacemaker (PPM) implantation plays a crucial role in managing heart rhythm abnormalities, ultimately improving the patient’s quality of life.